Ações afirmativas e a teoria da justiça de John Rawls - Franklin VinÍcius Marques Dutra (2019)
The subject of this work is the place of affirmative action in John Rawls's theory. To do so, we begin by drawing the relationship between justice as fairness and non-discrimination. Following, due to the lack of Rawlss manifestations on the subject, we present the views of some authors who have already worked out a Rawlsian justification for affirmative action. Among them, this work focuses on the interpretation proposed by Robert S. Taylor, for whom justice as fairness does not justify the existence of quotas even under non-ideal condition. The thesis raised here is that Taylor's reading is mistaken in both ideal and non-ideal conditions of justice. In the ideal case, the core of the problem arises from the question of the overcoming (or not) of systematic oppression in a well-ordered society. Since Taylor himself, in later text, seems uncertain about the matter, his argument becomes at least inconclusive. In addition, it is argued that Taylor did not correctly understand the lexical priority of principles, and that quotas do not conflict with formal equality of opportunity. Thus, affirmative action is supported by Rawls's ideal theory. Under non-ideal conditions, there are two central arguments to justify affirmative action. The first sets the limits of application of pure procedural justice and reconstructs the notion of pure proceduralism under non-ideal conditions in light of the reflective equilibrium. The second discusses the possibility of affirmative action based on a special form of the principle of difference, sensitive to inequalities not only of income and wealth and which considers the roles of non-ideal theory. In the end, if the project was successful, we state some arguments more favorable to Rawls's affirmative actions, attentive to the essential values of Rawls's liberalism, such as autonomy, individualism and proceduralism.